ANALISIS WACANA POLITIK KABAR PEMILU DALAM YOUTUBE CHANNEL TVONENEWS: KAJIAN PRAGMATIK - Wulandari S.; Yesi Pramudita (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
The purpose of this study is to describe the analysis of political discourse on the YouTube channel Kabar Pemilu. The method used in this study is descriptive with a qualitative approach. This method describes the data presented in the form of words that contain the meaning of the research results. The techniques used in data collection include observation, listening techniques, reading techniques, writing techniques, analysis techniques, documentation, and triangulation. The data analysis techniques used in this study include data collection, data reduction, data presentation, and drawing conclusions. Based on the research results "Analysis of Political Discourse in Election News on the YouTube Channel tvOneNews: A Pragmatic Study," it can be concluded that on the YouTube Channel tvOneNews, political discourse in the 2024 Election News contains four pragmatic categories, namely: 1) 90 deixis in the form of person, time, place, and discourse divided into two, namely, anaphora and cataphora), 2) 33 presuppositions in the form of existential, factive, lexical, nonfactive, and structural, 3) 3 implicatures in the form of conventional and nonconventional, and 4) 9 speech acts in the form of locution and illocution. Keywords: Discourse, Politics, 2024 Election, Pragmatics